A decade of volcanic construction and destruction at the summit of NW Rota‐1 seamount: 2004–2014. Issue 3 (1st March 2017) - Schnur, Susan R.; Chadwick, William W.; Embley, Robert W.; Ferrini, Vicki L.; de Ronde, Cornel E. J.; Cashman, Katharine V.; Deardorff, Nicholas D.; Merle, Susan G.; Dziak, Robert P.; Haxel, Joe H.; Matsumoto, Haru
Abstract: Arc volcanoes are important to our understanding of submarine volcanism because at some sites frequent eruptions cause them to grow and collapse on human timescales. This makes it possible to document volcanic processes. Active submarine eruptions have been observed at the summit of NW Rota‐1 in the Mariana Arc. We use remotely operated vehicle videography and repeat high‐resolution bathymetric surveys to construct geologic maps of the summit of NW Rota‐1 in 2009 and 2010 and relate them to the geologic evolution of the summit area over a 10 year period (2004–2014). We find that 2009 and 2010 were characterized by different eruptive styles, which affected the type and distribution of eruptive deposits at the summit. Year 2009 was characterized by ultraslow extrusion and autobrecciation of lava at a single eruptive vent, producing a large cone of blocky lava debris. In 2010, higher‐energy explosive eruptions occurred at multiple closely spaced vents, producing a thin blanket of pebble‐sized tephra overlying lava flow outcrops. A landslide that occurred between 2009 and 2010 had a major effect on lithofacies distribution by removing the debris cone and other unconsolidated deposits, revealing steep massive flow cliffs. This relatively rapid alternation between construction and destruction forms one end of a seamount growth and mass wasting spectrum. Intraplate seamounts, which tend to grow larger than arc volcanoes, experience collapse events that are orders of magnitude larger and much less frequent than those occurring at subduction zone settings. Our results highlight the interrelated cyclicity of eruptive activity and mass wasting at submarine arc volcanoes. Key Points: Repeat bathymetric mapping, ROV observations, and hydrophone records document changes in geology and eruptive style at NW Rota‐1 seamount Changes in eruptive activity between 2009 and 2010 impacted the type and distribution of geologic lithofacies at the summit of NW Rota‐1 Landslides are important agents of change at submarine arc volcanoes, and their frequency is controlled by cyclic eruptive activity